Pharmacological inhibition of fatty-acid oxidation synergistically enhances the effect of l-asparaginase in childhood ALL cells - Hermanova, I; Arruabarrena-Aristorena, A; Valis, K; Nuskova, H; Alberich-Jorda, M; Fiser, K; Fernandez-Ruiz, S; Kavan, D; Pecinova, A; Niso-Santano, M; Zaliova, M; Novak, P; et al. (Leukemia, 2016)
l-asparaginase (ASNase), a key component in the treatment of childhood acute lymphoblastic leukemia (ALL), hydrolyzes plasma asparagine and glutamine and thereby disturbs metabolic homeostasis of leukemic cells. The efficacy of such therapeutic strategy will depend on the capacity of cancer cells to adapt to the metabolic challenge, which could relate to the activation of compensatory metabolic routes. Therefore, we studied the impact of ASNase on the main metabolic pathways in leukemic cells. Treating leukemic cells with ASNase increased fatty-acid oxidation (FAO) and cell respiration and inhibited glycolysis. FAO, together with the decrease in protein translation and pyrimidine synthesis, was positively regulated through inhibition of the RagB-mTORC1 pathway, whereas the effect on glycolysis was RagB-mTORC1 independent. As FAO has been suggested to have a pro-survival function in leukemic cells, we tested its contribution to cell survival following ASNase treatment. Pharmacological inhibition of FAO significantly increased the sensitivity of ALL cells to ASNase. Moreover, constitutive activation of the mammalian target of rapamycin pathway increased apoptosis in leukemic cells treated with ASNase, but did not increase FAO. Our study uncovers a novel therapeutic option based on the combination of ASNase and FAO inhibitors.
Keywords: TOR Serine-Threonine Kinases; mTORC1; Humans; pyrimidiny; TOR serin-threoninkinasy; Mechanistic Target of Rapamycin Complex 1; oxidace-redukce; lidé; asparaginasa; autofagie; mastné kyseliny; monomerní proteiny vázající GTP; Monomeric GTP-Binding Proteins; nádorové buněčné linie; Oxidation-Reduction; multiproteinové komplexy; akutní lymfatická leukemie; Cell Line, Tumor; Autophagy; Pyrimidines; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Asparaginase; Multiprotein Complexes; Fatty Acids